The Effect of Brisk Walking on Blood Pressure of Hypertensive Patients - Utomo, Endrat Kartiko; Soleman, Sitti Rahma; AM, Ady Irawan (CV. Global Health Science Group, 2025)
Hypertension is one of the non-communicable diseases characterised by clinical symptoms of high blood pressure above ≥140/90 mmHg. one of the non-pharmacological implementations is physical activity or exercise, brisk walking physical activity is one way to control blood pressure in hypertensive patients. Objective to determine the effect of fast walking exercise on blood pressure of hypertensive patients. Quasy Experiment research method with Pre and Post Test with Control design, sampling technique with consecutive sampling with 48 respondents. fast walking exercise intervention for 20-30 minutes at a walking speed of 4-6 km / hour in the morning for 2 weeks. Blood pressure measurements were taken using a sphygmomanometer and analysed using Independent T - Test and paired T-Test. the average age was between 54 to 56 years old, female gender, the last education was high school, and the profession was labourer. There was a significant difference in systolic blood pressure with a P-value = 0.020*. While based on the results of the analysis of diastolic blood pressure between groups there was no significant difference in change with a P-value = 0.189 *. Fast exercise training for 20-30 minutes at a walking speed of 4-6 km / h in the morning for 2 weeks is able to reduce blood pressure in hypertensive patients, this shows that there is a great opportunity for hypertensive patients to improve their health and avoid complications.